P012 IL22 expression in intestinal immune cells is not augmented by AHR activation in health or Crohn's disease. (25th January 2019) - Harrow, P; Datta, R; Stagg, A; Lindsay, J O
Abstract: Background: IL-22 produced by mucosal immune cells plays an important role in maintenance of the intestinal barrier; production is increased in response to intestinal injury. The aryl hydrocarbon receptor (AHR) is a ligand-activated transcription factor that responds to specific dietary and bacterial ligands. In mice, activation of AHR is critical for the expression of IL22 . In diverse models of colitis, genetic deletion of AHR or low AHR ligand availability leads to reduced IL-22 activity and increased disease severity. Although enhancing IL-22 release by activating AHR is an attractive therapeutic approach it is unclear if this would reduce inflammation in the human IBD. In this study, we determine activation of AHR in vivo using quantitative measurement of CYP1A1 expression, which closely correlates with AHR activation, and examine the impact of AHR blockade or activation on IL22 expression in health and Crohn's disease. Methods: CD45+ cells isolated from endoscopic biopsies using antibody labelling and immunomagnetic sorting, were cultured with AHR ligand (FICZ 10 nM) or antagonist (CH-223191 100 μM). Whole biopsies were also immediately homogenised in RLT buffer and expression of AHR, CYP1A1, and IL22 determined by qRT-PCR. Results: Whole biopsies and CD45+ intestinal immune cells expressed both AHR and CYP1A1 ex vivo suggesting the presence of a functional AHR signalling pathway; AHR and CYP1A1 expression was higher in CD. IL22 expression was also detectable ex vivo but did not correlate with CYP1A1 expression and was lower in CD. AHR signalling was significantly inhibited by antagonist but was minimally enhanced by agonist. However, IL22 expression in vitro by CD45+ cells was not significantly affected by either AHR antagonist or agonist. Baseline AHR activation or response to agonist did not correlate with IL22 expression in response to agonist. However, the degree to which CYPY1A1 expression was inhibited by antagonist, a potential surrogate for in situ activation, did correlate with baseline IL22 expression in the same tissue suggesting a more complex relationship. Conclusions: In humans the AHR pathway is activated in vivo in both health and Crohn's disease. Resting IL22 expression is lower in CD compared with health. However, the expression of IL22 in intestinal immune cells was not augmented in vitro by AHR ligand in either health or disease, perhaps because the pathway is already near maximally activated. This suggests the relationship between AHR and IL22 is complex and simply supplementing AHR ligand intake may not be helpful in IBD.